Optimization method of transmission protsesa dannіh during sessions TCP-protocol - Хемраєв, А. К. (Problems of Informatization and Control, 2012)
The analysis of existent versions of protocol of ТСР is conducted, and also perspective decisions in area of management the transmission of packages at transport level of the Standard model of cooperation of the open systems. The row of lacks of mathematical models and methods, fixed in basis of this protocol is exposed, the removal of which is related to optimization of the proper parameters of networks. Approach is offered to the decision of task of optimization, based on the dynamic model of TCP-sessions and taking into account row of terms-limitations, directed on providing of the set indexes of quality and stability of TCP-sessions.